Penile Growth With Unusual Histopathology: A Case Report - Islam, SK Amirul; Islam, Md Monowarul; Nag, Shuvendra Nath; Rahman, Md Siddiqur; Karim, Howlader Fazlul; Chowdhury, Mohammad Murad; Arjuman, Farida; Saha, Pranashis (Bangladesh Journal of Urology, 2020)
Abstract Not Available Bangladesh Journal of Urology, Vol. 20, No. 2, July 2017 p.105-108